Estrutura e efeito de borda no componente arbóreo de um fragmento de floresta estacional semidecidual em Pernambuco - HOLANDA, Alan Cauê de (2008)
The forests are subject all types of disturbances, which can be natural or anthropic. The rupture of forests continuous for any of those factors causes the fragments formation, consequently it will form edge by exposing to factors abiotics, proposing decrease on biodiversity. This way, the present work aims to evaluate the edge effect and natural regeneration in forest semidecidual fragment, Mata do Alcaparra, Pernambuco. The fragment has 83ha, and it is located in Nazare da Mata-PE (7º44'00 " to 7º45 'S and 35º11'30 " to 35º12'30 "W), with predominance of soils Yellow Red Podzólicos. The climate, according classification of Köppen is As'. The amostral area was implanted with 10 transectos (10 x 100m) perpendicular to edge. The transect were subdivided in contiguous plots of 10 x 10 m for evaluation of edge effect; and for natural regeneration sub-plots of 10 x 1 m were located inside of plots. Were measures all the individuals with CAP ≥ 15 cm for the evaleation of the edge effect, and for the natural regeneration was measures individuals with height upper 1m and CAP ≤ 14,9 cm. After that, they were calculated phytossociologic and statistical parameters for density and basal area. Thus, were found 72 táxons in arboreal community and 77 táxons in natural regeneration, besides the forest fragment has a great diversity of species in arboreal community (3,29 nats/ind.) and natural regeneration (3,08 nats/ind.); Until the 100m analyzed, the fragment is under edge effect, which was not observed statistical differences between the densities and basal areas analyzed.